P48 A joint respiratory and palliative care clinic: the patient experience. (12th November 2019) - Nathoo, N; Devani, N; Brusse, R; Craig, R; Mandal, S
Abstract : Background: There are a growing number of patients in the community with chronic debilitating respiratory disease. Early identification, assessment and management of their symptoms and their own and their family's psychosocial needs can improve quality of life and prevent unnecessary hospital admissions. We present our findings from a newly established joint Respiratory and Palliative Care clinic which aimed to identify patients with chronic respiratory illness and address their chronic symptoms and psychosocial needs using an MDT approach. Specifically, the clinic aimed to address symptom control, emotional needs, future-planning, support for relatives/carers, and provide information about community services. Method: Patients attending the joint clinic were asked to complete a standardised questionnaire after clinic, to assess their experience. Results: 12 patients completed the questionnaire. The diagnoses of the patients were advanced COPD (n=4), motor neurone disease (n=2) and chronic hypercapnic respiratory failure requiring NIV (n=4), obstructive sleep apnoea (n=1) and severe bronchiectasis (n=1). Prior to attending clinic, 87.5% (n=7/8) were aware of the referral and reason for it. Seventy-five per cent (n=6/8) believed the clinic was informative, 62.5% (n=5/8) felt it was supportive, and 25% (2/8) felt relieved about the referral. Fifty per cent (n=4/8) felt anxious prior to the clinic and 25% (n=2/8) thought it would be unnecessary. Patient experiences after the clinic appointment have been summarised in table 1. Assessment of utility was undertaken using a likert scale of 0 – 10 (with 0='not useful at all' and 10=very useful). Conclusion: A joint respiratory and palliative care clinic involving dedicated discussions for patients with chronic debilitating respiratory disease is favoured by patients with a mean satisfaction score of 8.75. All patients believed they had enough time to discuss any concerns, felt involved in decision-making and would recommend the clinic. However, our data suggests that more focus needs to be spent on issues such as providing information about community support services and support for relatives and carers. Furthermore, perceived utility scores for many of the interventions are lower than we expected. This highlights that further work is required to identify exactly what is important for patients or what areas perhaps have been under-addressed during previous consultations to avoid duplication.